BUDGET FEDERALISM AS AN INTEGRAL PART OF UKRAINE’S GLOBALIZATION INTEGRATION - P. Ustynova, Iryna; A. Tolkachova, Iryna; Ya. Lykhova, Sofiia; A. Husar, Olga; V. Stepanenko, Viacheslav (Revista Gênero e Interdisciplinaridade, 2021)
The relevance of the researched problem is conditioned by the civilizational need of globalization entry of Ukraine in the European and world community with further reforming of its system of state administration in the financial sphere. The purpose of the article is based on the study of current world experience and the consequences of budget federalization as a phenomenon, analysis of the current reform situation in Ukraine and the development of useful recommendations for further approbation. The basic method is comparative, which allowed to compare different state and legal systems, in order to identify similarities or differences between them, resulting in a qualitative state of the legal system as a whole and individual legal institution. This allowed us to consider the problem in a holistic manner and from every side. The article analyzes the policy and experience of budget federalism of Ukraine and other countries, analyzes the development of budget legislation of Ukraine and develops recommendations for the Ukrainian legislator for further structural changes in the administration of the financial sector. It is claimed that Ukraine has done significant work in adapting its legislation to European and world practices through the introduction of budget (fiscal) federalism. Recommendations, analysis and review are aimed at adaptation of Ukrainian legislation to world economic systems during the process of globalization and embedding Ukraine in it. The materials of the article can be useful to anyone who researches federalism.